Sailing into the wind: Exploring the relationships among ambidexterity, vacillation, and organizational performance - Boumgarden, Peter; Nickerson, Jackson; Zenger, Todd R. (Strategic Management Journal, 2012)
Abstract While sustainable high performance requires the capacity to simultaneously explore and exploit, the management literature is divided on the most feasible and efficient route toward this end. We review two proposed approaches for achieving simultaneously high levels of exploration and exploitation: organizational ambidexterity and organizational vacillation. To facilitate comparison, we map these approaches onto a common performance landscape, making precise the empirical question of which delivers superior long run performance. We then analyze canonical cases from both literatures, examining patterns of decision making and corresponding performance over time. These cases suggest that vacillation may offer higher long run performance than ambidexterity, while ambidexterity enhances performance on the margin when utilized within larger epochs of vacillation. We conclude that ambidexterity and vacillation are complements with respect to performance, albeit through different mechanisms. Copyright © 2012 John Wiley & Sons, Ltd.